Planetary health and environmental sustainability in African health professions education - James H. Irlam; Charlotte Scheerens; Bob Mash (AOSIS, 2023)
CliMigHealth and the Education for Sustainable Healthcare (ESH) Special Interest Group of the Southern African Association of Health Educationalists (SAAHE) call for the urgent integration of planetary health (PH) and environmental sustainability into health professions curricula in Africa. Education on PH and sustainable healthcare develops much-needed health worker agency to address the connections between healthcare and PH. Faculties are urged to develop their own 'net zero' plans and to advocate for national and sub-national policies and practices that promote the Sustainable Development Goals (SDGs) and PH. National education bodies and health professional societies are urged to incentivise innovation in ESH and to provide discussion forums and resources to support the integration of PH into curricula. Contribution: This article provides a position statement for integrating planetary health and environmental sustainability into African health professions education curricula.